Palynology of the Palaeogene and Neogene from the Warmia and Mazury areas (NE Poland) - Słodkowska, Barbara (Geologos, 2009)
Pollen, phytoplankton and microfauna from the Palaeogene and Neogene of two boreholes in NE Poland have been studied. Borehole Klucznik 1 is located in the Warmia area, and borehole Sąpłaty 3 borehole in the Mazury area. The oldest palynomorph assemblage comes from the Klucznik sediments; it consists of phytoplankton from the Early Palaeocene (Danian) D1 and D2 dinocyst zone, and from the Selandian D3 zone. The Eocene is present in the both the Klucznik and the Sąpłaty successions. The Middle Eocene assemblage has been dated as late Bartonian and belongs to the D11 dinocyst zone. The Late Eocene (Priabonian) D12 dinocyst zone is also present in both boreholes. Sporomorphs of a Late Eocene palynomorph assemblage point on the proximity of land and on terrestrial vegetation. The dinocyst zone D13, characteristic for the earliest Oligocene ('Latdorfian') has been found in both profiles as well. A Neogene sporomorph assemblage dating from the Middle Miocene (Early Serravallian) occurs only in the Sąpłaty profile. This sporomorph assemblage is correlated with pollen zone VIII. Pollen zone IX is present in the uppermost part of the Middle Miocene (Middle Serravallian). Late Miocene deposits (Late Tortonian) with pollen zone XI are present, too. The Miocene deposits accumulated in densely vegetated swamps, resulting now in the occurrence of lignite. The sedimentary conditions in the Warmia and Mazury regions were identical during the Neogene and Palaeogene, implying that both provinces belonged at the time to one sedimentary basin.